(3EbGeI GdMLI GdHGgQI Ydi gOe cfGFS eUQ hGdbGgQIs - (3GdOefghQj , CMeO Hf YHO GdefYe Hf jhSa Hf UjGe GdOefghQj, SQGL GdOjf,J (B1192 (3g` s
(3ChdgG (B:s
(3hHYO gPG eG GdJeS efi HYV GdeYJHQjf GddhPYjI ef HjGf Mce GdcfGFS HeUQ hGdbGgQI GdeYRjI s
(3BNQgG (B:s
(3hCf jMaX YdjfG QCS MGdfG hgh GdEjeGf Je HMeO Gddg hYhfg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B164 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B303s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B110s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY (B318) s
Keywords: (3Gdabg GdMfajs